FIQH SUNDA - Fahrurrozie, Rendra; Misno, Misno (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2023)
The scholars have different theories concerning Islam coming to Nusantara. They believed that the first community to accept Islam was the residents of the coastal areas of Sumatera, Java, Sulawesi, Kalimantan, Maluku, Nusa Tenggara, and Papua. Afterward, Islam was disseminated to rural areas throughout the Nusantara including fiqh (Islamic jurisprudence), one of the fundamental teachings of Islam. This reception was surely through a long process and resistance from the indigenous residents of the Nusantara who already had local religions and beliefs practiced continuously by hereditary generations. Badui in Banten and Kampung Naga, West Java were indigenous residents of the island. This article seeks to discuss the negotiating process of fiqh among Badui and Kampung Naga’s communities from historical and anthropological viewpoints. This article argues that the negotiating of fiqh by the community of Badui is limited to particular cases such as marriage and inheritance. While the community of Kampung Naga receives the majority of fiqh. The negotiating of fiqh in both communities was influenced strongly by their interaction with outside communities and also state power.